Workshop on the place and role of women in the dairy value chain of Bobo-Dioulasso (Burkina Faso) - Fayama, Tionyéléé; Dabire, Der; Orounladji Boko, Michel; Ouattara Songdah, Désiré (2024)
The present research project, initiated as part of the Work Package 5 activities of the CGIAR Initiative on Agroecology on "Understanding and influencing changes in partnerships and behavior", focused on the role and place of women in the dairy industry. The data collected during the study leaded by Fayama et al (2024), on women's place and role in Bobo Dioulasso's dairy value chain, was presented and discussed during a workshop held in Bobo-Dioulasso in November 2024. The proceedings of this workshop are presented in this report.